Sex structure and timing of spawning for Mercenaria stimpsoni (Bivalvia, Veneridae) in the northwestern Japan Sea - Roman V. Vlasenko; Marianna V. Kalinina (Известия ТИНРО, 2015)
Sex structure, growth, maturing and spawning of clam Mercenaria stimpsoni at Primorye coast (Japan Sea) are considered on the data of histological analysis of gonad tissue preparations and gonad smears collected in diving surveys conducted eastward from Cape Povorotny in the summer-fall of 2006-2009 and 2012-2013. The mollusk dwells on sandy or muddy-sandy grounds at the depth to 20 m along the coast opened to surf waves. Its annual increments were identified in radial section of the outer layer of shell between the umbo and ventral margin. Its mature begins at the age 7-8 years with the shell length about 40 mm; all mollusks become mature at the age 10-11 years when their shell reaches the size 50-55 mm, so transition from juvenile to mature clam lasts about 3 years. The shell length of half-maturing is 43.5 mm that corresponds to the age 9-10 years. Males prevail among small-sized M. stimpsoni (40-44 mm) with the ratio 1.26 : 0.74, but the sex ratio is equal for the basic mature stock, and females prevail among large-sized clams with the ratio 0.70 : 1.30, so the sex ratio for the whole surveyed area is approximately equal. M. stimpsoni spawns there from mid-August to mid-September, with the mass spawning in late August - early September, under the water temperature 13-19оC.